Pelajaran Geografi pada Kurikulum Berbasis Kompetensi - Mochamad Enoh (Universitas Negeri Malang, 2016)
The implementation of the competence Based Curriculum as a tool to reach the national education objectives is inevitable; however, it should not be at the expense of a particular science. This happens with geography, because the Competence Based Curriculum (CBC) integrates geography lesson into Physics and Economics in the Senior High School (SMU) curriculum. This integration leads to the vague status of geography as a branch of science with its unique charac-teristics. The draft of CBC 2001 does not explicitly state Geography as a subject and it has caused considerable restlessness among geo-graphy teachers, lecturers, and students of the Geography Education Department. With the integration of Geography into other subjects, there is a possibility that in the long run Geography will no longer exits as a subject. Therefore, it is necessary to review the draft of Com-petence Based Curriculum 2001 which is still in the phase of try out.